The Effect of Role Play Method Towards Cooperation Capability of Kids Age 5-6 Years Old - Wihardjo, R. Sihadi Darmo; Nurani, Yuliani; Ramadhan , Syahrul (International Journal of Psychosocial Rehabilitation, 2020)
This research was conducted with the aim to determine the effect of the method of playing role on the ability of cooperation in children aged 5-6 years at TK Ros Ros Regency of Bima. This research is a quasi experimental study with a pretest-posttest control group research design. The population in this study were 79 children with the sample used were 61 children. The sample is then divided into 2 groups. The technique of determining the sample is to use random sampling techniques. The validity of the contents of the instrument used in this study was calculated using the Gregory formula. Meanwhile for instrument reliability, it is estimated by using Cronbach’s alpha formula. Data collection techniques in this study were observation and interview techniques. Furthermore, for data analysis techniques, the Anova test was used and analyzed using the SPSS 22 program.The results showed that the role playing method had a significant influence on the ability of cooperation. This is indicated by the value of p <sig (0.05) which means that there is an influence between the method of playing role on the ability of cooperation in children aged 5-6 years at Bunga Ros Kindergaten, Regency of Bima.